A Novel Bandpass Filters Using Complementary Split Ring Resonator Loaded Half Mode Substrate Integrated Waveguide - Jiang, Di; Xu, Yuehang; Xu, Ruimin; Lin, Weigan (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A half mode substrate integrated waveguide with hexagon shaped complementary split-ring resonators (CSRRs) etched on the top of the waveguide is presented in this paper. The simulated results show that extra low insertion loss of about -0.1 dB and the return loss of -10 dB can be achieved. The proposed structure allows the implementation of a forward wave below the characteristic cutoff frequency of the waveguide. By changing the radius of the hexagon shaped CSRR, which is incorporated on top of the waveguide, the pass frequency band can be tuned easily. Finally, a compact band pass filter is fabricated and validated.